Nuclear Training Classes Asked for Maritime School - Vallejo Times-Herald (Vallejo Times-Herald)
Congressman John F. Baldwin has asked the Atomic Energy Commission to use facilities of the California Maritime Academy and the maritime academies of Maine, New York and Massachusetts in its proposed program for training merchant marine crews to operate nuclear power plants. Baldwin, whose Sixth Congressional District includes Solano and Contra Costa counties made his recommendation in a letter to Richard P. Godwin, administrator of the Maritime Branch of the Atomic Energy Commission.